Comparison of upfront transplantation and pretransplant cytoreductive therapy for advanced myelodysplastic syndrome - Wang, Hong; Li, Yan; Xu, Qingyu; Zhou, Wei; Yin, Chengliang; Wang, Ruiqi; Wang, Mengzhen; Xu, Yuanyuan; Li, Yonghui; Yu, Li (Clinical lymphoma, myeloma & leukemia, 2021)
Background - Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only curative therapy for advanced myelodysplastic syndrome (MDS). However, the value of pretransplant cytoreduction remains debatable. - Patients and Methods - We retrospectively compared the outcomes of upfront transplantation and pretransplant cytoreduction. Of 69 patients, 39 received upfront allo-HSCT and 30 received pretransplant cytoreduction, including chemotherapy (n = 16), hypomethylating agents (HMAs, n = 6), and HMAs with chemotherapy (n = 8). - Results - The upfront group achieved similar overall survival (OS) and a trend of better progression-free survival (PFS) from diagnosis compared with the cytoreduction group (3-year PFS, 64.0% vs. 44.4%, P = .076). Posttransplant outcomes were comparable between the two groups in terms of OS, relapse-free survival (RFS), cumulative incidence of relapse (CIR), and non-relapse mortality (NRM). In patients with ≥2 mutations, the upfront group achieved better OS and PFS (3-year OS, 100.0% vs. 68.6%, P = .044; 3-year PFS: 92.3% vs. 43.9%, P = .016) than the cytoreduction group. Patients achieving remission in the cytoreduction group had outcomes similar to the upfront group, but those without remission before transplantation had a significantly worse posttransplant OS (3-year OS, 46.7% vs. 75.7%, P = .038). Patients with pretransplant HMAs had better PFS than those with chemotherapy or HMAs plus chemotherapy (P < 0.05). - Conclusion - Compared with pretransplant cytoreduction, upfront allo-HSCT might provide more benefit to some patients with advanced MDS if there are suitable donors. HMAs would be a good alternative during the donor search.
Gesehen am 26.01.2023